2011
DOI: 10.5551/jat.6197
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Two AMI Risk Factors: Low Serum Lipoprotein Lipase Mass and Hypoadiponectinemia

Abstract: Aim: Recent clinical studies have reported that low lipoprotein lipase mass in preheparin serum (s-LpL) and hypoadiponectinemia are important risk factors for acute myocardial infarction (AMI). The aim of this study was to elucidate the relationship between low s-LpL and hypoadiponectinemia, both of which are risk factors for AMI. Methods: One hundred and thirty-seven male patients with AMI and fifty-three males with normal coronary arteries (NCA) were enrolled in the study. Coronary risk factors, including s-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Although the RLP-TG/RLP-C ratio in pre-heparin plasma exhibited a trend of being inversely correlated with the LPL concentration in the fasting plasma, it was not statistically significant, probably because of a low TG concentration in the fasting plasma. Adiponectin is a plasma protein expressed in adipose tissue that is known to be closely associated with LPL and cardiovascular risk [38]. Interestingly, adiponectin in pre-heparin plasma was inversely and significantly correlated with the RLP-TG/RLP-C ratio and positively correlated with LPL concentration, but adiponectin was not correlated with LPL activity in post-heparin plasma.…”
Section: Discussionmentioning
confidence: 98%
“…Although the RLP-TG/RLP-C ratio in pre-heparin plasma exhibited a trend of being inversely correlated with the LPL concentration in the fasting plasma, it was not statistically significant, probably because of a low TG concentration in the fasting plasma. Adiponectin is a plasma protein expressed in adipose tissue that is known to be closely associated with LPL and cardiovascular risk [38]. Interestingly, adiponectin in pre-heparin plasma was inversely and significantly correlated with the RLP-TG/RLP-C ratio and positively correlated with LPL concentration, but adiponectin was not correlated with LPL activity in post-heparin plasma.…”
Section: Discussionmentioning
confidence: 98%
“…Plasma EL concentration was shown to be associated with inflammation 27, 28) . Some studies showed that HL was associated with insulin resistance and inflammation 29, 36) , and LPL was significantly associated with insulin resistance, adiponectin, and inflammation 30, 37, 38) . Therefore, in our study, we like to propose that triglyceride lipases affecting CAD or in-stent restenosis could work through other mechanisms such as inflammation.…”
Section: Discussionmentioning
confidence: 99%